Valuation of upstream oil and gas assets. (3rd May 2019) - George, Bob; Cline, Bill; Seager, Rawdon
Abstract: This article addresses the valuation of upstream oil and gas assets – hydrocarbon reserves and resources - within a conceptual framework intended to be clear to non-technically-trained or experienced readers. The first part of the article addresses in detail the mechanics of quantifying the underlying hydrocarbon volumes, translating these into (the expectation of) future cash flows which underpin value, and the incorporation of risk. The second part of the article focuses in more detail on utilizing the cash flow analysis to create a valuation opinion, and validating that opinion using other market metrics (which can also be used on occasions where the data required for a cash flow analysis is not available). It also comments upon a number of issues and considerations that come into play and may underlie the differences or be the cause of contention between parties who assert very different opinions of value. The whole valuation process requires bringing together a large number of considerations, many of which are subject to considerable uncertainty. Care must therefore be taken not to imply an accuracy in the opinion concluded which, in reality, will almost certainly have a reasonable range of uncertainty that sometimes can be quite wide.